An exploratory study examining the core affect hypothesis of the anti-depressive and anxiolytic effects of physical activity - Rebar, Amanda; Faulkner, G.; Stanton, R. (Elsevier BV, 2015)
© 2015 Elsevier Ltd. We propose the core affect hypothesis that physical activity enhances valence and activation for people with depression symptoms but only valence for people with anxiety symptoms. In an exploratory study, affective valence and activation were assessed before and after a bout of exercise at a self-selected intensity in a small sample of inpatients. For most people with depressive disorders, affective valence (57%) and activation (55%) increased; whereas for people with anxiety disorders, half (50%) experienced an increase in affective valence, but only some (35%) experienced increased activation. Although exploratory and underpowered to test for statistically significant differences, these findings provide tentative support for more robust exploration into the core affect hypothesis. It may be that practitioners can enhance the impact of physical activity on depression or anxiety symptoms by applying the core affect hypothesis.